Dark reign Elektra. - writer, Zeb Wells ; penciler, Clay Mann ; inker, Mark Pennington (Marvel Publishing, 2009)
"She's the deadliest woman in the world... and she's never been in worse shape. Broken, beaten, and tortured by alien scientists, Elektra stumbles to freedom in the aftermath of the Skrull invasion. Now she struggles and fights to stay barely alive, and to clear her name for atrocities committed by an impostor. A lot of people want Elektra killed... and in her state, that shouldn't be too difficult!"--Publisher description.